AKIBAT HUKUM WANPRESTASI PROSES BALIK NAMA SERTIPIKAT HAK MILIK DALAM JUAL BELI TANAH - Risky Widnyana, I Wayan; Sri Rahayu Gorda, Anak Agung Ayu Ngurah (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2022)
Land has a very important role for human life because everyone needs land during life until death. Land in Indonesia has a very important role to support life in society. The need for land will increase along with the growth of the population, all of whom need land to live and continue their lives, therefore there are more and more processes of buying and selling land, but in the process of buying and selling land there is still a breach of contract in the sale and purchase agreement. after the sale and purchase process should proceed to the land registration process to obtain a certificate, but this has not been done. The importance of registering land that has changed ownership so that the plot of land has legal certainty and avoids a dispute.